2021
DOI: 10.1038/s41396-021-00898-x
|View full text |Cite
|
Sign up to set email alerts
|

Depth-discrete metagenomics reveals the roles of microbes in biogeochemical cycling in the tropical freshwater Lake Tanganyika

Abstract: Lake Tanganyika (LT) is the largest tropical freshwater lake, and the largest body of anoxic freshwater on Earth’s surface. LT’s mixed oxygenated surface waters float atop a permanently anoxic layer and host rich animal biodiversity. However, little is known about microorganisms inhabiting LT’s 1470 meter deep water column and their contributions to nutrient cycling, which affect ecosystem-level function and productivity. Here, we applied genome-resolved metagenomics and environmental analyses to link specific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 72 publications
5
67
0
1
Order By: Relevance
“…8 ). This is in agreement with metagenomic studies of various ecosystems recovering the genetic potential for most, if not all, N transformation pathways ( 26 , 54 57 ). Despite the overall similarities in the N cycling potential, ecosystems harbor unique N transforming microbial communities forming complex networks ( 1 ).…”
Section: Discussionsupporting
confidence: 89%
“…8 ). This is in agreement with metagenomic studies of various ecosystems recovering the genetic potential for most, if not all, N transformation pathways ( 26 , 54 57 ). Despite the overall similarities in the N cycling potential, ecosystems harbor unique N transforming microbial communities forming complex networks ( 1 ).…”
Section: Discussionsupporting
confidence: 89%
“…The presence of even a small number of Cyanobacteria at the anoxic bottom of the lake is surprising considering their association with aerobic metabolism. However, this has been observed elsewhere (Tran et al 2021). Actinobacteria are known to include the cosmopolitan epilimnetic lineage acI (order Nanopelagicales), and account for much of the abundance in the epilimnion.…”
Section: Taxonomy -Phylamentioning
confidence: 91%
“…The most coarse taxonomic level, phylum, was a natural starting point to visualize the most general trends in the microbiome. The relative abundance of phyla has been shown to change dramatically with depth in several other depth-discrete sampling studies (Tran et al 2021;Rojas-Jimenez et al 2021;Baatar et al 2016;Garcia et al 2013). These changes in phyla are often attributed to the redox gradients throughout the water column (Jones, Newton, and McMahon 2009;Wu and Hahn 2006;Newton et al 2007;Garcia et al 2013) .…”
Section: Taxonomy -Phylamentioning
confidence: 96%
See 1 more Smart Citation
“…Scaffolds used to benchmark performance were acquired from nine separate publicly available datasets spanning eight unique metagenomes from marine 48,49 , freshwater [50][51][52] , human gut 53 , and soil environments 54,55 . Details on the studies, scaffolds, reads, and accession numbers can be found in Supplemental Table 11 Each dataset was processed separately.…”
Section: Performance Validation Datasets and Metricsmentioning
confidence: 99%